Religiosity and Consumerism: An Autopsy on Ideological Paradoxes in Islamic Religious Congregation - Retnani Srinarwati, Dwi; Setiawan, Rahmat; Qomaru Zaman, Akhmad (KnE Social Sciences, 2024)
The Majelis Taklim, rooted in Salafi principles, fundamentally interprets Islam based on the Al Quran and the sunnah of Prophet Muhammad. A significant number of Majelis Taklim members belong to the bourgeois class. This bourgeois inclination bears specific implications for the culture of consumerism and the ideology of capitalism, prompting a thought-provoking inquiry into the connection between the Salafi madhab and the culture of consumerism. To decipher this enigma, the concepts of Ideology and Consumerism become the theoretical framework in this research. This study adopts a phenomenological approach, utilizing statements from multiple subjects who are members of Majelis Taklim and also serve as the data sources. The data collection technique is an open interview to explore a more empirical narrative, and the data analysis technique used in this research is interpretation. The data analysis shows a paradox between the aspects of religiosity that are comprehended and the social practices in acts out. This paradox occurs because (1) high-branded products are a symbol of social class in their circle; (2) adopting a glamorous style does not violate Majelis Taklim doctrine; and (3) their entry into the community is driven by a desire to undergo hijrah and broaden social connections. Keywords: salafi, religiosity, consumerism, capitalism, ideology